(untitled) (KYAMC Journal, 2013)
This study was conducted to evaluate the efficacy, safety and adverse effects of topical clindamycin phosphate 1% lotion in treating acne vulgaris in a group of Bangladeshi people. This prospective study was undertaken in skin & VD out patient department of Rajshahi Medical college Hospital, Rajshahi. A total of 30 patients, 15 (50%) males and 15 (50%) females between ages 15 and 35 years (mean 18 years) with acne of grades I, II and III of duration <3 years to 10 years (mean 3.33 years) were studied. Clindamycin phosphate 1% lotion was administered twice daily for 12 weeks to each patient. Response was excellent in 73.33%, good in 20%, fair in 3.33% and poor in 3.33% of cases. Clinical adverse effects were noted in 20% of cases where oiliness was in 6.67%, irritation and burning in 3.33%, puritans in 3.33%, erythema i3.33% and peeling in 3.33% of cases. None of the reactions was severe, all were mild and well tolerated and most occurred within the first month of initiation of treatment and resolved with continued use of drug and completely cured after the treatment completed. No body had to discontinue the therapy for side effects. 80% of the total patients had no side effects. This study confirms that clindamycin is safe and effective topical therapy for mild to moderate acne vulgaris. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13316 KYAMC Journal Vol.1(2) January 2011, 59-64